Hybrid Integration Strategies: Combining the Strengths of mmWave and Sub-6 GHz Technologies - Thaar A. Kareem (Misan Journal of Engineering Sciences)
Abstract: It is necessary to observe that the technologies used in the field of radio transmission and wireless communications determine the features and efficiency of networks. Given the ever-increasing need for high-speed wireless communication, Millimeter-wave (mmWave) and sub-6 GHz technologies have been developed and integrated into current communication systems. This article summaries the comparison between these two different frequency bands regarding their unique advantages, disadvantages, and their uses, while emphasizing more in their advantages. We consider hybrid integration solutions capitalizing on complementary characteristics of both frequency bands in order to achieve improved performance in 5G and beyond networks. mmWave frequencies offer high data rates and large bandwidth that is required by applications requiring extremely fast connectivity. Due to the limited range and sensitivity to obstructions, sub-6 GHz frequencies are required; however, the coverage and penetration through the obstructions are higher. By combining these technologies, hybrid systems can ensure smooth communication, increase dependability, and improve the spectrum utilization. As it considers the technical challenges, possible solutions, and performance gain of hybrid mmWave and sub-6 GHz integration, this article points out the role of increasingly sophisticated antenna designs, beamforming methods and smart spectrum control array This research gives insight into the future of wireless communication by analyzing through simulation experiments and thorough analysis of the essential elements whose successful deployment is needed in order to utilize the benefits of hybrid systems.